Efforts to Maintain the Health of Pregnant Women through Antenatal Care Education - Desi Oktariana (Conferences of Medical Sciences Dies Natalis, 2020)
In Indonesia, maternal mortality is still an important problem that requires comprehensive treatment and follow-up. Maternal Mortality Rate (MMR) is still high and has not reached the target set by the government. Maternal mortality can be prevented through Antenatal Care (ANC) services. ANC visit, for example, is influenced by the knowledge and attitudes of pregnant women. Unfortunately, there are still pregnant women who don't know about the importance of ANC, so they don't make ANC visits. This community service activity is carried out to provide education, in the form of counseling, for pregnant women about Antenatal Care (ANC), with the aim of increasing awareness of pregnant women to maintain health during pregnancy and increase the participation of pregnant women in ANC visits.